Tailoring the Surface Chemical Reactivity of Transition‐Metal Dichalcogenide PtTe2 Crystals. (9th February 2018) - Politano, Antonio; Chiarello, Gennaro; Kuo, Chia‐Nung; Lue, Chin Shan; Edla, Raju; Torelli, Piero; Pellegrini, Vittorio; Boukhvalov, Danil W.
Abstract: PtTe2 is a novel transition‐metal dichalcogenide hosting type‐II Dirac fermions that displays application capabilities in optoelectronics and hydrogen evolution reaction. Here it is shown, by combining surface science experiments and density functional theory, that the pristine surface of PtTe2 is chemically inert toward the most common ambient gases (oxygen and water) and even in air. It is demonstrated that the creation of Te vacancies leads to the appearance of tellurium‐oxide phases upon exposing defected PtTe2 surfaces to oxygen or ambient atmosphere, which is detrimental for the ambient stability of uncapped PtTe2 ‐based devices. On the contrary, in PtTe2 surfaces modified by the joint presence of Te vacancies and substitutional carbon atoms, the stable adsorption of hydroxyl groups is observed, an essential step for water splitting and the water–gas shift reaction. These results thus pave the way toward the exploitation of this class of Dirac materials in catalysis. Abstract : Herein, it is demonstrated how the inert surface of PtTe2 can be transformed into a catalyst by implanting Te vacancies and by surface functionalization with substitutional carbon atoms. The stable adsorption of hydroxyl groups represents an essential step for water splitting and the water–gas shift reaction. These results pave the way toward the exploitation of Dirac materials in catalysis.